Studi Perencanaan Bangunan Ipal Di Desa Blang Beurandang, Kabupaten Aceh Barat - Meylis Safriani; Cut Suciatina Silvia (Universitas Teuku Umar, 2018)
Iom Housing Blang Beurandang Village is a dense neighborhood where the population consists of 56 families with 160 people. Based on the preliminary survey, every household in IOM Housing already has a toilet. However, it does not yet have wastewater treatment in a septic tank. Based on these problems, it is necessary to plan the installation of communal waste treatment to improve the sanitation system in this village. Data collection in this study with primary data collection and secondary data. Primary data includes interviews and site surveys as location of IPAL planning (to obtain data on the characteristics of waste water in Blang Beurandang Village). Secondary data include population data, house number data, and topographic map of planning area. The design result obtained dimension of IPAL Building is planned to have length 11 m and width of building 3.25 meter. This building consists of several spaces including an inlet tub with dimensions of 1.15 m long and 3.25 m wide, tub settler with a length of 4.00 m and 3.25 m width, dividing tub with length of 0.80 m and width of 3, 25 m, tub filter (tub media filter) with a length of 1 m and a width of 1 m of 12 pieces and outlet with a length of 1 m and width of 1 m. In the filter basin is used biofilter in order to grow bacteria with anaerobic system. Biofilter is usually used which is fabrication. However, in the design of this WWTP biofilter used from the materials used plastic bottles are recycled in order to reduce waste and also to save the cost of development expenditure. Keywords: waste, waste treatment, installation of communal waste treatment